STUDENTS’ LANGUAGE ACQUISITION THROUGH THE INTEGRATION OF EXTENSIVE READING INTO SPEAKING TASKS IN EFL CLASSROOMS - Sumardi, Sumardi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This study explores how pedagogical strategies for integrating extensive reading into speaking tasks should be designed for EFL students and whether such integration had the potential to enhance students’ language acquisition. A qualitative case study was employed, and twenty undergraduate students participated in the study. Interviews and observation were used as the data collection methods. Data were analyzed using a thematic analysis. The findings revealed that students who had previously struggled to read longer texts became well-motivated to engage with a wide range of reading materials across various genres. They also believed that the tasks encouraged them to read a variety of texts, gain more knowledge about ‘the new worlds’ and could eventually speak confidently. The integration of extensive reading and speaking tasks created a natural atmosphere for students’ language acquisition by enhancing their mastery of contextual vocabulary and other language elements. Therefore, EFL teachers are encouraged to integrate this approach into their courses as findings indicated that extensive reading integrated into speaking tasks provided rich language input, allowed for better cognitive processing, and cultivated students’ motivation, confidence, and communicative competence through active exposure to various genres.